2019
DOI: 10.1093/jxb/erz536
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate regulation of lateral root and root hair development in plants

Abstract: Nitrogen (N) is one of the most important macronutrients for plant growth and development. However, the concentration and distribution of N varies in soil due to a variety of environmental factors. In response, higher plants have evolved a developmentally flexible root system to efficiently take up N under N-limited conditions. Over the past decade, significant progress has been made in understanding this form of plant ‘root-foraging’ behavior, which is controlled by both a local and a long-distance systemic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 100 publications
(168 reference statements)
3
41
1
Order By: Relevance
“…In this study, LRs were almost inhibited in the high-NUE variety LY9348 ( Figure 1 B). This result is contradictory to that in Arabidopsis , where LRs are largely induced by N shortage [ 80 , 88 , 89 , 90 , 91 , 92 ]. Therefore, the absorption area increments on the RSA by LR initiation and elongation may not be the key mechanism underlying increased N absorption efficiency in LY9348, especially compared with the LRs in Arabidopsis .…”
Section: Discussioncontrasting
confidence: 79%
“…In this study, LRs were almost inhibited in the high-NUE variety LY9348 ( Figure 1 B). This result is contradictory to that in Arabidopsis , where LRs are largely induced by N shortage [ 80 , 88 , 89 , 90 , 91 , 92 ]. Therefore, the absorption area increments on the RSA by LR initiation and elongation may not be the key mechanism underlying increased N absorption efficiency in LY9348, especially compared with the LRs in Arabidopsis .…”
Section: Discussioncontrasting
confidence: 79%
“…The regulation of nitrate acquisition involves the modulation of nitrate uptake and root system growth (Guan et al ., 2014; Naulin et al ., 2019; Jia and Wirén, 2020; Liu et al ., 2020). Regulatory systems of low‐ and high‐affinity NITRATE TRANSPORTER ( NRT ) expression by nitrogen availability have been extensively studied (Kiba and Krapp, 2016).…”
Section: Cytokinins Play a Role In The Regulation Of Nitrate Acquisitmentioning
confidence: 99%
“…Emerging evidence has shown that some small peptides of the C-TERMINALLY ENCODED PEPTIDE (CEP) and CLAVATA3/EMBYO SURROUNDING REGION-related (CLE) families are responsive to N/Pi signals and are involved in modulation of RSA (Liu et al 2020, Taleski et al 2018. Upon induction, they are perceived and bound by their respective receptors, CEP receptor (CEPR) and CLAVATA (CLV), to relay the signals to downstream components.…”
Section: Peptidesmentioning
confidence: 99%
“…Among these strategies, molecular breeding via transgenic approaches require a fully understanding of the gene regulatory networks (Tian et al 2012). While the number of the genes in these networks is boosting (Liu et al 2020, Liu andWirén 2017), several recognized issues and emerging areas deserve more attention.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation